2019
DOI: 10.1002/qj.3571
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atmosphere–ocean coupling on the prediction of 2016 western North Pacific tropical cyclones

Abstract: We examine the merit of atmosphere-ocean coupled models for tropical cyclone (TC) predictions in the western North Pacific (WNP), where accurate TC predictions remain challenging. The UK Met Office operational atmospheric global numerical weather prediction (NWP) model is compared with two trial coupled configurations, in which the operational atmospheric model is coupled to a one-dimensional mixed-layer ocean model and a three-dimensional dynamical ocean model. Reforecasts for the 2016 TC season show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Cooler SSTs to the right of the TC track drive the TC towards the relatively warmer SSTs to its left. The leftward displacement of TC tracks in CPL agrees with other studies of coupled models (Khain & Ginis, 1991;Wu et al, 2005), although some authors have also found rightward displacement (Bender et al, 1993) or both leftward and rightward 250 displacement (Feng et al, 2019).…”
Section: Tropical Cyclone Track Errorssupporting
confidence: 90%
See 1 more Smart Citation
“…Cooler SSTs to the right of the TC track drive the TC towards the relatively warmer SSTs to its left. The leftward displacement of TC tracks in CPL agrees with other studies of coupled models (Khain & Ginis, 1991;Wu et al, 2005), although some authors have also found rightward displacement (Bender et al, 1993) or both leftward and rightward 250 displacement (Feng et al, 2019).…”
Section: Tropical Cyclone Track Errorssupporting
confidence: 90%
“…Lewis et al, 2019). Most previous studies show that air-sea coupling reduces TC 70 intensity (Feng et al, 2019;Mogensen et al, 2017;Neetu et al, 2019;Takaya et al, 2010;Zarzycki, 2016; https://doi.org/10.5194/wcd-2021-46 Preprint. Discussion started: 26 July 2021 c Author(s) 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Further details on these forecasts can be found in Feng et al . (2019), which analysed the same three sets of forecasts for West Pacific tropical cyclones.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing KPP and ATM shows the effects of thermodynamic air-sea coupling; comparing NEMO and ATM shows the effects of thermodynamic and dynamic coupling (i.e., including the ocean dynamical response); comparing NEMO and KPP shows the effects of ocean dynamics within the coupled system. Further details on these forecasts can be found in Feng et al (2019), which analysed the same three sets of forecasts for West Pacific tropical cyclones.…”
Section: Metum Forecastsmentioning
confidence: 99%
“…As highlighted in the latest reports of WMO's International Workshop on Tropical Cyclones (IWTC), research carried out over the last four years has considerably improved our understanding of TC intensification processes [1,2], as well as TC tracking and intensity forecasting [3,4]. The operational implementation of coupled ocean-atmosphere (OA) numerical weather prediction (NWP) systems by many national weather services has, in particular, played a key role in reducing forecasting errors at all space and time scales [5][6][7][8]. Despite these important advances, additional efforts are still needed to accurately predict and characterize the potential impacts of tropical cyclones on a given territory, especially during landfall.…”
Section: Introductionmentioning
confidence: 99%